Code-Mixing and Code-Switching of Indonesian Celebrities: A Comparative Study - Nana Yuliana; Amelia Rosa Luziana; Pininto Sarwendah (Lingua Cultura, 2015)
Foreign language skill presents a language variety called code-mixing and code-switching. The purpose of this study was to get some information to identify the types of code mixing and code switching frequently used by Indonesian celebrities. The study was divided into two groups. Group I was inclusive of the celebrities with native speakers parents and Group II comprised celebrities capable of speaking two or more languages. The qualitative and quantitative methods were used to analyze the code mixing and code switching with different frequency. It can be concluded that Group II use code-mixing and code-switching with a different frequency and speak foreign language more active.